Pelatihan Pembersihan Toilet untuk Pelaku Usaha Homestay dan Jasa Wisata di Parapat - Ritonga, Abdul Kadir; Tauhid, Booni; Hamdani, Muhammad; Deffie, Robert; Ahmad, Andora Yusuf (Universitas Negeri Padang, 2021)
The community service program is designed to improve the ability and knowledge of business actors and tourism services through training held in Parapat and attended by twenty participants for business and tourism services. The methods used are socialization, tutorials, discussions, and field practice. The material includes the definition of toilets and their uses, types of toilets, cleaning and preparing guest bathrooms, techniques and procedures, and preparing and retooling bathrooms. The results of this training activity are expected that the participants can gain knowledge and skills in cleaning toilets.